Wireless power transfer system with aligned two transmitters and one receiver for power distribution system in smart buildings - You, Hyun Woo; Park, Jung Hoon; Lee, Byoung Hee (Journal of Power Electronics, 2022)
Intelligent houses and skyscrapers require many electronic devices for the smart control of building conditions. These devices make the power distribution system of buildings too complicated and expensive. Wireless power transfer (WPT) systems are one of the more promising candidates that simplifies power distribution systems. WPT systems via magnetic resonance coupling (MRC) can transmit power further and broader than WPT systems via inductive coupling. Moreover, recent architectures use an H-beam structure due to its durability and recyclability. Since the H-beam structure can be used as a guidance for WPT systems, the performance of the WPT system can be improved. Thus, this paper proposes a WPT system via MRC with aligned two transmitters (2-Txs) and one receiver to simplify the power distribution systems in smart buildings and to improve the power capability of WPT systems. The characteristics of a WPT system with 2-Txs according to variation of coil arrangement, coil size, and distance imbalance are investigated and verified by mathematical analysis and experimental results. In addition, a phase-shift control method is adopted and experimentally verified to control the output power without an additional power conversion circuit.
Keywords: Beam structures; Building conditions; Magnetic resonance coupling; Magnetic resonance couplings; Multi-transmitter; One receivers; Phase shift control; Power-distribution system; Smart control; Wireless power transfer; Magnetic resonance coupling (MRC); Multi-transmitter; Phase-shift control; Wireless power transfer (WPT)